2007
DOI: 10.1108/14637150710834587
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing customer relationship management

Abstract: Purpose -The bursting of the e-bubble affected expectations with regard to mobile initiatives and willingness to invest in them very negatively. Business managers request detailed and thorough analyses prior to engaging in mobile initiatives. The paper aims to present a method, with which mobile business can be introduced to the customer relationship management (CRM) field. Design/methodology/approach -The paper follows the design science paradigm as outlined by March and Smith, and Hevner et al. Findings -The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…These could indicate the uncertainty of the return on investment, the lack of specific competencies, the lack of information sharing between business and service or application providers (Valsecchi et al , 2007). Schierholz et al (2007) identified other barriers to adopting mobile technologies including the internal and external controls, organisational readiness and mobile technological compatibility such as the internal and external controls, organisational characteristics/readiness and mobile technological characteristics/compatibility. Chen and William (1993) believe that consideration of SMEs characteristics is important in order to avoid the danger of technical determinism.…”
Section: Proposed Mcrm Strategy Framework For Uk Smesmentioning
confidence: 99%
See 3 more Smart Citations
“…These could indicate the uncertainty of the return on investment, the lack of specific competencies, the lack of information sharing between business and service or application providers (Valsecchi et al , 2007). Schierholz et al (2007) identified other barriers to adopting mobile technologies including the internal and external controls, organisational readiness and mobile technological compatibility such as the internal and external controls, organisational characteristics/readiness and mobile technological characteristics/compatibility. Chen and William (1993) believe that consideration of SMEs characteristics is important in order to avoid the danger of technical determinism.…”
Section: Proposed Mcrm Strategy Framework For Uk Smesmentioning
confidence: 99%
“…Strategy is crucial to a firm's successful adoption of new technology (Tzokas and Saren, 1997) but more importantly, organisations must implement it properly (Schierholz et al , 2007). Ghingold and Johnson (1998) point out that the potential of mobile channel capabilities needs to be fully explored in the development of services to meet the key objectives and responsibilities of marketing in the future.…”
Section: Proposed Mcrm Strategy Framework For Uk Smesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mobile commerce develop means of selling goods and services for the companies, to the clients and sending crucial information to customers and employees of the company at anywhere and anytime [51].…”
Section: A Positive Points About M-commercementioning
confidence: 99%